Chaos Theology: A New Approach to the Science-Theology Dialogue - Bonting, Sjoerd Lieuwe (Zygon, 1999)
Comparison of the concepts of creation from chaos and creation out of nothing (creatio ex nihilo) leads me to reject the latter for several reasons: it is not the biblical concept, and it presents serious conceptual, scientific, and theological problems. Chaos theology is outlined under the headings creation from chaos; chaos and contingency; chaos, evil, and creativity; chaos and incarnation; chaos and eschatology. It is shown to be well suited for the science-theology dialogue by some examples of its application to aspects of cosmic and biological evolution: initial mystery, separation and ordering; chaos and entropy; contingency and fine-tuning of the universe; purpose and progressiveness in evolution; and complexity theory and chaos events.